The relationship of The elected group and the currents of the Algerian national movement between (1927-1937) - Abdelhafid, Bouabdallah (The Algerian Historical Journal, 2026)
The Algerian patriotism, despite its ideological diversity, crystallized in the rejection of the French colonial laws that made the Algerians foreigners in their homeland, and the period between the two world wars witnessed the birth of political and cultural movements that engaged in fighting and confronting this policy. Create elites who carried the hopes and aspirations of society towards dignity and equality, the most prominent of which was the independence, reform and inclusion movement. The thirties were full of events and political interactions imposed by the transformations that France itself experienced and the resulting different positions between the currents of the national movement that ranged from rapprochement and sometimes alliance to disharmony and antagonism Other times.